(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Introduction: Open Fracture shaft of tibia is a common orthopaedic problem due to subcutaneous nature of bone, usually managed operatively. The usual operative modalities used for fixation of open fractures are the cast and braces, dynamic compression plate (DCP), external fixator and intramedullary nail (IMN). Postoperative complications reported after intramedullary nailing is infection 12.09%. Union after intramedullary nailing is 85.48%. Intramedullary nailing is the more common surgical treatment option for open tibial diaphyseal fractures (type I and II). Objectives:- To determine outcome of reamed intramedullary interlocking nail in tibial diaphyseal fractures in terms of frequency of union and wound infection. Material & Methods Study Design: - Quasi Experimental Study Setting: The study was conducted in Orthopedic Department of Allied and DHQ Hospital Faisalabad. Duration of Study: - Eight months after the approval of synopsis. From 10-12-2012 to 10-08-2013 Results: 120 patients were included in study, 90 were males and 34 females. Patients were followed for wound infection at 12th postoperative day and union at 24 weeks.109 (87.90%) patients had no infection and 15(12.09%) patients developed infection. 106(85.48%) fractures healed in 24 weeks and 18(14.52%) either went into delayed union or non union. Conclusion: It is concluded that reamed intramedullary interlocking nailing is a good mode of internal fixation in type I and II open fractures of tibia as it allows early weight bearing, minimizes the chances of infection and delayed union and has led to union in maximum cases.